POLA ASUH KELUARGA DAN PERKEMBANGAN EMOSIONAL ANAK PRA SEKOLAH - WANDA, RUNI; NYOKO, YUNETI OCTAVIANUS; KODY, MARTHA METI; AGUSTINE, ULY (Poltekkes Kemenkes Kupang, 2017)
Introduction:The family is the first and main vehicle for character education. If a family fails to educate character on its children, it will be difficult for other institutions outside the family to improve it and will affect the child's own emotional development. Based on the observation of some students who have not been active during the learning process is going on, often disrupt his friends while playing, fighting and grabbing toys. The purpose of this research is to know the description of the pattern of family care and emotional development of preschool children in SatapWaingapu kindergarten 4. Method: used is descriptive study, population in this research are family and preschool children as many as 35 people and the sample using Total Sampling. Results: Democratic family pattern of 30 people (86%), authoritarian 5 people (14%) and negative child emotional development that is 24 people (69%), positive as many as 11 people (31%). Suggestions: Families are expected to be able to understand and understand the importance of parenting in children, have a lot of time in children and to educational facilities to better pay attention to children's activities and children's play environment in school.